The Battle of Iwo Jima : a resource bibliography and documentary anthology - Sandberg, Walt, 1935-2004 (McFarland & Company, 2005)
"Part One, offers information on more than 800 books, magazines, official documents, audio-visual materials and online resources about the Battle of Iwo Jima. Part Two, offers the texts of hard-to-locate documents; a series of maps showing the day-by-day progression of the battle; and a selection of poetry inspired by the battle"--Provided by publisher.